Hybrid evolutionary algorithm for multi-mode resource-constrained project scheduling problem - Marshal, Brian. (2011)
Scheduling problem is ubiquitous in many industries. However, real industrial scheduling problem can sometimes become too complicated. Therefore, specific problems are formulated as instances that can be studied in detail; one of which is known as the Multi-mode Resource-Constrained Project Scheduling Problem (MRCPSP). Solving MRCPSP itself is very challenging since, up to now, no polynomial approach is able to solve it optimally.